Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.3389/fphar.2017.00829
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Pogostone on 2,4,6-Trinitrobenzenesulfonic Acid-Induced Experimental Colitis via Inhibition of T Helper Cell

Abstract: Inflammatory bowel disease (IBD) is a chronic immune-related disease mainly caused by the disequilibrium of T helper (Th) cell paradigm? Pogostone (PO) is one of the major chemical constituents of Pogostemon cablin (Blanco) Benth. The present study aims to investigate the potential benefit of PO against IBD in a 2,4,6-trinitrobenzenesulfonic acid (TNBS)-induced experimental colitis model. PO treatment by enema significantly brought down the disease activity index (DAI) of the TNBS-challenged rats, which was ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…From Day 8~14, health status including body weight, food and water consumption, and disease activity index (DAI) were recorded daily. DAI was scored according to the criteria in Table 1 as described previously with mild modification (Mi et al, 2020; Su et al, 2017), that is DAI = (weight loss score + feces consistency score + hemafecia score) / 3. On the 15th day, all animals were bled from orbital plexus, and then sacrificed by cervical dislocation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…From Day 8~14, health status including body weight, food and water consumption, and disease activity index (DAI) were recorded daily. DAI was scored according to the criteria in Table 1 as described previously with mild modification (Mi et al, 2020; Su et al, 2017), that is DAI = (weight loss score + feces consistency score + hemafecia score) / 3. On the 15th day, all animals were bled from orbital plexus, and then sacrificed by cervical dislocation.…”
Section: Methodsmentioning
confidence: 99%
“…The colons were opened longitudinally. Macroscopic colonic inflammation was scored according to the criteria in Table 2 as described previously with mild modification (Luk, Ko, Fung, & Cho, 2002; Su et al, 2017). Finally, colons were segmented and stored appropriately for different purposes at once.…”
Section: Methodsmentioning
confidence: 99%
“…CD4 + T cells mainly contain effector CD4 + T cells such as T helper 1 (Th1), Th2, Th17, and regulatory T cells (Tregs). Studies have shown that intestinal immune homeostasis depends on the regulation and balance of these CD4 + T cell subgroups, and the deregulated overexpansion and activation of Th1 and Th17 cells in relation to Tregs can lead to intestinal inflammation, such as IBD [1012]. Since Th1 and Th17 cells could secrete large amounts of proinflammatory cytokines such as IFN- γ , TNF- α , IL-1 β , and IL-17, resulting in persistent intestinal inflammation [13], medications that can suppress colonic oxidative status and inhibit Th1/Th17 responses would be shown to be clinically effective.…”
Section: Introductionmentioning
confidence: 99%
“…Pogostone (PO) is one of the major chemical constituents of Pogostemon cablin (Blanco) Benth. In a study by Su et al, PO improved the inflammatory state, reducing effects on the infiltration of total Th cells into the inflammatory colon, especially pro-inflammatory Th1, and pro-inflammatory cytokine levels (202).…”
Section: Chinese Herbal Medicinementioning
confidence: 97%